Quasi-solid-state lithium-sulfur battery and preparation method thereof
By using a combined design of high-sulfur-soluble polymer and low-sulfur-soluble polymer in lithium sulfur batteries, combining high-concentration lithium salts and weak polar plasticizers, a synergistic effect of "sulphur-resistance" and "buckle sulfur" is formed in lithium sulfur batteries. , solves the problem of sulfur species dissolution and instability of the lithium negative electrode interface in lithium sulfur batteries, and significantly improves the utilization rate and circulation stability of the battery.
Patent Information
- Application Number
- CN202411370527.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
AI Technical Summary
Existing lithium-sulfur batteries use quasi-solid polymer electrolytes to cause the loss of active substances caused by the dissolution of sulfur species into the electrolyte and the unstable interface of lithium negative electrodes, resulting in low reversible capacity at room temperature, short cycle life, and low Coulomb efficiency, making it difficult to meet practical needs. .
Using a battery design including a sulfur-based positive electrode, a quasi-solid polymer electrolyte and a lithium-based negative electrode, the high concentration of lithium salt and weak polarity plasticizer are used through the combination of high sulfur-soluble polymer and low sulfur-soluble polymer. The synergistic effect of "sulphur resistance" and "buckle sulfur" is formed to limit sulfur species to the positive electrode structure, and to improve electrode reaction kinetics and interface stability through conductive agents and compound additives.
It effectively solves the problems of sulfur species loss and negative electrode unstable interface, improves the utilization rate of active substances and battery cycle stability, and improves the reversible capacity, Coulomb efficiency and safety performance of the battery.
Smart Images

Figure CN119230931A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a quasi-solid-state lithium-sulfur battery and a preparation method thereof. Background Art
[0002] At present, solid polymer electrolytes for lithium-sulfur batteries mostly use polyethylene oxide (PEO) polymers. Due to the high crystallinity of PEO, it is not conducive to the movement of polymer chain segments. The ionic conductivity of solid polymer electrolytes prepared using it is generally low. For this reason, it is usually necessary to further introduce liquid plasticizers to construct a quasi-solid polymer electrolyte system. On the one hand, it can improve the room temperature ionic conductivity of the electrolyte, and on the other hand, it can improve the solid-solid interface contact.
[0003] However, PEO can produce strong interactions with polysulfides, resulting in obvious sulfur dissolution problems in the PEO solid phase. Some of these dissolved sulfur species remain in the electrolyte and gradually lose their activity due to separation from the conductive phase, while the other part passes through the electrolyte to the negative electrode side under the action of concentration gradient and electric field force, corroding and passivating the lithium negative electrode, resulting in high negative electrode interface impedance and uneven lithium deposition. If liquid plasticizers are introduced into PEO to construct a quasi-solid polymer electrolyte, sulfur species may also accelerate entry into the electrolyte through these plasticizing components and diffuse and migrate toward the negative electrode. At this time, the loss of active substances and lithium corrosion problems are more difficult to control.
[0004] In summary, the main defects of existing lithium-sulfur batteries using quasi-solid polymer electrolytes are the loss of active materials caused by the dissolution of sulfur species into the electrolyte and the instability of the lithium negative electrode interface. The above defects result in low reversible capacity, short cycle life, and low coulombic efficiency of the battery at room temperature, and the overall performance is difficult to meet practical requirements. Summary of the invention
[0005] In order to overcome the above technical problems, the purpose of the present invention is to provide a quasi-solid-state lithium-sulfur battery and a preparation method thereof. The method aims to construct a combined system in which the positive electrode promotes sulfur dissolution and the electrolyte inhibits sulfur dissolution, which can completely confine the sulfur species in the positive electrode structure, effectively solve the problems of positive electrode sulfur species loss and negative electrode unstable interface, and at the same time promote the in-situ, rapid and full conversion of sulfur species to ensure the overall performance of the quasi-solid-state lithium-sulfur battery.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A quasi-solid-state lithium-sulfur battery comprises a sulfur-based positive electrode, a quasi-solid-state polymer electrolyte and a lithium-based negative electrode, wherein the sulfur-based positive electrode comprises a sulfur-containing active material and a high sulfur-soluble polymer, and the quasi-solid-state polymer electrolyte comprises a lithium salt, a weak polar plasticizer and a low sulfur-soluble polymer, wherein the lithium salt concentration reaches 90% to 100% of its saturated solubility in the weak polar plasticizer.
[0008] The high sulfur-soluble polymer includes at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyacrylamide (PAM), and copolymers and derivatives of these polymers.
[0009] The low sulfur-soluble polymer includes at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyionic liquid, polyester, polysulfone, and copolymers and derivatives of these polymers.
[0010] The weak polar plasticizer includes at least one of cyclopentyl methyl ether, dipropylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, fluoroether, anisole, cyclohexane, diethyl ether, 1,2-diethoxyethane, 1,4-dioxane, ionic liquid, alkane, and aromatic hydrocarbon.
[0011] The lithium salt includes at least one of LiODFB, LiBOB, LiPF6, LiTFSI, LiNO3, LiBF4, LiClO4, LiFSI, LiBETI, LiCF3SO3, LiAsF6, LiTf, LiOTf, LiBC2O4F2, LiN(FSO2)2, LiN(CF3SO2)2, LiFAP, LiFAB, and LiTFSM.
[0012] The sulfur-containing active materials include elemental sulfur, sulfur-based composite materials, polysulfides (Li2S n , at least one of 4≤n≤8).
[0013] The lithium-based negative electrode includes at least one of lithium metal, lithium-carbon composite material, lithium-silicon alloy, and alloy formed by lithium and metal.
[0014] The sulfur-based positive electrode further contains a conductive agent, which includes at least one of nano carbon black, carbon nanotubes, graphene, and carbon nanofibers.
[0015] The sulfur-based positive electrode also contains a lithium salt additive, and the lithium salt additive includes at least one of LiODFB, LiBOB, LiPF6, LiTFSI, LiNO3, LiBF4, LiClO4, LiFSI, LiBETI, LiCF3SO3, LiAsF6, LiTf, LiOTf, LiBC2O4F2, LiN(FSO2)2, LiN(CF3SO2)2, LiCl, LiI, LiBr, LiF, LiFAP, LiFAB, and LiTFSM.
[0016] The mass ratio of the sulfur-containing active material, the high sulfur-soluble polymer, the conductive agent and the lithium salt additive is (60-95):(5-30):(0-10):(0-10).
[0017] The quasi-solid polymer electrolyte further contains a compound additive, wherein the compound additive includes at least one of sulfide, oxide, nitride, fluoride, and metal organic framework.
[0018] The mass ratio of the plasticizer, the low sulfur-soluble polymer and the compound additive is (20-40): (50-80): (0-10), and the concentration of the lithium salt in the weak polar plasticizer reaches (3-8) mol / L.
[0019] A method for preparing a quasi-solid-state lithium-sulfur battery comprises the following steps:
[0020] S1: The sulfur-containing active material, the high sulfur-soluble polymer, the conductive agent, and the lithium salt additive are uniformly mixed in an organic solvent, and the obtained slurry is coated on the surface of the conductive current collector. After the solvent evaporates, a highly uniform lamellar sulfur-based positive electrode is obtained;
[0021] S2: High-concentration lithium salt, weak polar plasticizer, low sulfur-soluble polymer and compound additive are mixed evenly in an organic solvent, and the obtained slurry is poured into a flat mold or coated on the surface of the sulfur-based positive electrode. After the solvent evaporates, a thin-film quasi-solid polymer electrolyte with highly uniform properties is obtained;
[0022] S3: stacking the sulfur-based positive electrode, quasi-solid polymer electrolyte, and lithium-based negative electrode in sequence, and encapsulating them to obtain a quasi-solid-state lithium-sulfur battery.
[0023] Beneficial effects of the present invention:
[0024] The present invention utilizes the differences in the sulfur-dissolving abilities of different polymers, combined with high-concentration lithium salts and weakly polar plasticizers, to carry out a matching linkage design for the sulfur-based positive electrode and the quasi-solid polymer electrolyte, which can form a synergistic effect of "sulfur blocking" of the electrolyte and "sulfur binding" of the positive electrode in the quasi-solid-state lithium-sulfur battery, fully confine the sulfur species within the positive electrode structure and promote their in-situ full conversion, while improving the interface structural chemistry of the lithium-based negative electrode, thereby improving the overall utilization rate of active materials and the battery cycle stability.
[0025] The high sulfur-soluble polymer, due to its strong solvation effect, can interact strongly with the sulfur species in the positive electrode, thereby forming a strong bond to the sulfur species and inhibiting its escape from the positive electrode, that is, forming the positive electrode "sulfur binding" function. At the same time, the high sulfur-soluble polymer has good affinity and solubility for sulfur species, which can promote the conversion and formation of polysulfides during the charge and discharge process (similar to the formation of a double potential platform in a liquid electrolyte), which is conducive to improving the electrode reaction kinetics, so that the sulfur species confined in the positive electrode are in situ, quickly, and fully converted, and the conversion efficiency of the active material is improved. In addition, the high sulfur-soluble polymer also essentially plays the role of an electrode binder to maintain the stability of the sulfur-based positive electrode structure.
[0026] The weak polar plasticizer and the low sulfur solubility polymer have very weak affinity and interaction with sulfur species. At the same time, the lithium salt concentration reaches or approaches its saturated solubility in weak polar solvents, so that almost all plasticizers are used to complex lithium salts, and the excess free plasticizer provided to sulfur species in the electrolyte is very limited, resulting in extremely low solubility of sulfur species in plasticizers containing high concentrations of lithium salts. Therefore, the quasi-solid polymer electrolyte forms three "sulfur-blocking" factors of high concentration lithium salts, weak polar plasticizers and low sulfur solubility polymers, which can jointly resist the dissolution of sulfur species in the positive electrode into the electrolyte.
[0027] Furthermore, the low sulfur-soluble polymer has high mechanical strength and a wide stable potential window, which can ensure the mechanical / electrochemical stability of the electrolyte skeleton.
[0028] Furthermore, the weakly polar plasticizer can wet the positive and negative electrodes, improve the solid-solid interface contact, and at the same time has a chemical / electrochemical film-forming effect on the lithium metal surface, which can stabilize the lithium negative electrode / electrolyte interface, and regulate the uniform deposition of lithium ions and curb the growth of dendrites.
[0029] Furthermore, the lithium salt concentration reaches or approaches its saturated solubility in weakly polar solvents, which can provide sufficient lithium sources for the electrolyte and ensure the ionic conductivity and lithium ion migration number of the electrolyte. At the same time, since lithium salts are enriched in weakly polar solvents and relatively scarce in polymer skeletons, a special local high-concentration environment is formed in the quasi-solid electrolyte, which makes it easy to generate more contact ion pairs and aggregates in the lithium ion coordination structure, prompting more anions to enter the solvation structure, and then inducing the formation of inorganic anion-derived interface films on the surface of the lithium negative electrode, thereby enhancing the stability of the negative electrode interface.
[0030] Furthermore, the sulfur-containing active material is not limited to elemental sulfur or sulfur-based composite materials, and polysulfides can also be selected. Polysulfides themselves contain lithium sources, can conduct lithium ions, and have higher ion conductivity than traditional elemental sulfur or sulfur-based composite materials. In theory, they are more suitable for quasi-solid-state lithium-sulfur batteries.
[0031] Furthermore, the lithium-based negative electrode is not limited to lithium metal, and lithium-carbon composite materials, lithium-silicon alloys, and alloys formed by lithium and metals can also be selected. These composite materials or alloys can regulate the uniform deposition of lithium metal and inhibit the volume expansion and dendrite growth of the negative electrode.
[0032] Furthermore, the conductive agent is added to the positive electrode to improve the electronic conductivity of the sulfur-based positive electrode.
[0033] Furthermore, the lithium salt additive is added to the positive electrode to improve the ionic conductivity of the sulfur-based positive electrode.
[0034] Furthermore, the compound additives added to the quasi-solid polymer electrolyte can reduce the crystallinity of the polymer skeleton and promote ion conduction, or these compound additives can further strengthen the negative electrode interface film and inhibit interface side reactions through reduction decomposition.
[0035] The present invention also relates to a method for preparing a quasi-solid-state lithium-sulfur battery, which is simple to operate, has a controllable process, and is easy to implement. In order to ensure the overall properties of the sulfur-based positive electrode and the quasi-solid polymer electrolyte and give full play to the expected efficacy, the present invention limits the mass ratio of the sulfur active material, the high sulfur-soluble polymer, the conductive agent, and the lithium salt additive in the positive electrode, the mass ratio of the weak polar plasticizer, the low sulfur-soluble polymer, and the compound additive in the electrolyte, and the concentration of the lithium salt in the weak polar plasticizer.
[0036] In summary, the quasi-solid-state lithium-sulfur battery constructed using the method of the present invention can effectively solve the defects of lithium-sulfur batteries using traditional quasi-solid-state polymer electrolytes, and has outstanding advantages such as high active material utilization, high Coulomb efficiency, long-term cycle stability, balance between specific energy and specific power, and good safety performance, and has significant innovation and technological progress. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a cycle performance diagram of the quasi-solid-state lithium-sulfur battery prepared in Example 1.
[0038] Figure 2 This is a charge and discharge curve diagram of the quasi-solid-state lithium-sulfur battery prepared in Example 1.
[0039] Figure 3 This is the cycle performance diagram of the traditional quasi-solid-state lithium-sulfur battery prepared in Comparative Example 1. DETAILED DESCRIPTION
[0040] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0041] Example 1
[0042] A quasi-solid-state lithium-sulfur battery, wherein the sulfur-based positive electrode is prepared by dissolving sulfur-carbon composite material, PEO, nano carbon black and LiTFSI (additive) in NMP at a mass ratio of 70:10:10:10, coating on the surface of aluminum foil and volatilizing the solvent. The quasi-solid polymer electrolyte is prepared by dissolving LiTFSI (main salt), DMM, PVDF and LLZTO in DMF, coating on the surface of a flat mold, and forming an independent electrolyte membrane after solvent volatilization and demoulding. Among them, the concentration of LiTFSI reaches 100% of its saturated solubility in DMM, and the mass ratio of DMM, PVDF and LLZTO is 30:65:5. The above-mentioned sulfur-based positive electrode, solid polymer electrolyte and lithium metal negative electrode are stacked and packaged to obtain a quasi-solid-state lithium-sulfur battery.
[0043] The lithium-sulfur battery obtained above was subjected to constant current charge and discharge test at room temperature, with a charge and discharge rate of 0.1C and a voltage window of 1.7-2.8V. After 100 cycles, the cycle performance and charge and discharge curves are shown in Figure 2. Figure 1 and Figure 2 As shown in the figure, it can be seen that the battery has a high reversible capacity and good cycle stability. Two discharge platforms are observed on the discharge curve, indicating that polysulfide intermediates can be normally transformed and formed in the battery structure.
[0044] Example 2
[0045] A quasi-solid-state lithium-sulfur battery, wherein the sulfur-based positive electrode is composed of a sulfur-carbon composite material, PAN, and carbon nanofibers in a mass ratio of 70:20:10, and the quasi-solid-state polymer electrolyte is composed of LiBETI, an ionic liquid Pyr 14 TFSI, polyionic liquid, Si3N4, in which the concentration of LiBETI reaches its concentration in Pyr 14 95% of the saturation solubility in TFSI, Pyr 14 The mass ratio of TFSI, polyionic liquid and Si3N4 is 40:57:3. The rest is the same as in Example 1.
[0046] Example 3
[0047] A quasi-solid-state lithium-sulfur battery, wherein the sulfur-based positive electrode is composed of a sulfur / graphene composite material, PMMA, and LiODFB (additive) in a mass ratio of 60:30:10, and the quasi-solid-state polymer electrolyte is composed of LiFSI (main salt), CPME, and PVDF-HFP, wherein the concentration of LiFSI reaches 90% of its saturated solubility in CPME, and the mass ratio of CPME to PVDF-HFP is 20:80. The rest is the same as in Example 1.
[0048] Example 4
[0049] A quasi-solid-state lithium-sulfur battery, wherein the sulfur-based positive electrode is coated on the surface of a porous carbon substrate by Li2S6, PEO and carbon nanotubes in a mass ratio of 75:20:5, and the quasi-solid-state polymer electrolyte is coated on the surface of the sulfur-based positive electrode by LiTFSI, TEGDME / fluorinated ether TTE mixed plasticizer (1:1 volume ratio), PVDF, and P2S5, wherein the concentration of LiTFSI reaches 100% of its saturated solubility in TEGDME / TTE, and the mass ratio of TEGDME / TTE, PVDF, and P2S5 is 40:50:10. The negative electrode is a lithium-indium alloy. The rest is the same as in Example 1.
[0050] Comparative Example 1
[0051] A quasi-solid-state lithium-sulfur battery, wherein the sulfur-based positive electrode is a sulfur-carbon composite material, PVDF and carbon nanotubes (80:10:10 mass ratio) dissolved in NMP and coated on the surface of aluminum foil. The quasi-solid polymer electrolyte is LiTFSI, DME / DOL mixed plasticizer (volume ratio 1:1) and PEO dissolved in acetonitrile and coated on the surface of the sulfur-based positive electrode. The concentration of LiTFSI in DME / DOL is 1 mol / L, the mass ratio of DME / DOL and PEO is 40:60, and the negative electrode is lithium metal. The rest is the same as Example 1.
[0052] The lithium-sulfur battery obtained above was subjected to constant current charge and discharge test at room temperature. The charge and discharge system was the same as that in Example 1. The cycle performance test results were as follows: Figure 3 As shown in the figure, although the initial capacity of the battery is high, the cycle performance is very poor. The reversible capacity retained after 100 cycles is very limited, and the average coulombic efficiency is low, indicating that there are serious problems of active material loss and lithium corrosion in the battery system.
[0053] The electrochemical performance data of Example 1 and Comparative Example 1 are compared, and the results are shown in Table 1. It can be seen that compared with the quasi-solid-state lithium-sulfur battery prepared by the traditional method, the quasi-solid-state lithium-sulfur battery prepared by the method of the present invention has obvious advantages in terms of reversible capacity, coulombic efficiency and cycle stability, and the overall performance of the battery is more excellent.
[0054] Table 1 Test results of Example 1 and Comparative Example
[0055]
[0056] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A quasi-solid-state lithium-sulfur battery, characterized in that: The invention comprises a sulfur-based positive electrode, a quasi-solid polymer electrolyte and a lithium-based negative electrode. The sulfur-based positive electrode comprises a sulfur-containing active material and a polymer with high sulfur solubility. The quasi-solid polymer electrolyte comprises a lithium salt, a weak polar plasticizer and a polymer with low sulfur solubility. The concentration of the lithium salt reaches 90% to 100% of its saturated solubility in the weak polar plasticizer.
2. A quasi-solid-state lithium-sulfur battery according to claim 1, characterized in that: The high sulfur-soluble polymer includes at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyacrylamide (PAM), and copolymers and derivatives of these polymers.
3. A quasi-solid-state lithium-sulfur battery according to claim 1, characterized in that: The low sulfur-soluble polymer includes at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyionic liquid, polyester, polysulfone, and copolymers and derivatives of these polymers.
4. A quasi-solid-state lithium-sulfur battery according to claim 1, characterized in that: The weak polar plasticizer includes at least one of cyclopentyl methyl ether, dipropylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, fluoroether, anisole, cyclohexane, diethyl ether, 1,2-diethoxyethane, 1,4-dioxane, ionic liquid, alkane, and aromatic hydrocarbon; The lithium salt includes at least one of LiODFB, LiBOB, LiPF6, LiTFSI, LiNO3, LiBF4, LiClO4, LiFSI, LiBETI, LiCF3SO3, LiAsF6, LiTf, LiOTf, LiBC2O4F2, LiN(FSO2)2, LiN(CF3SO2)2, LiFAP, LiFAB, and LiTFSM.
5. A quasi-solid-state lithium-sulfur battery according to claim 1, characterized in that: The sulfur-containing active materials include elemental sulfur, sulfur-based composite materials, polysulfides (Li2S n , 4≤n≤8); The lithium-based negative electrode includes at least one of lithium metal, lithium-carbon composite material, lithium-silicon alloy, and alloy formed by lithium and metal.
6. A quasi-solid-state lithium-sulfur battery according to claim 1, characterized in that: The sulfur-based positive electrode further contains a conductive agent, which includes at least one of nano carbon black, carbon nanotubes, graphene, and carbon nanofibers.
7. A quasi-solid-state lithium-sulfur battery according to claim 6, characterized in that: The sulfur-based positive electrode also contains a lithium salt additive, and the lithium salt additive includes at least one of LiODFB, LiBOB, LiPF6, LiTFSI, LiNO3, LiBF4, LiClO4, LiFSI, LiBETI, LiCF3SO3, LiAsF6, LiTf, LiOTf, LiBC2O4F2, LiN(FSO2)2, LiN(CF3SO2)2, LiCl, LiI, LiBr, LiF, LiFAP, LiFAB, and LiTFSM.
8. A quasi-solid-state lithium-sulfur battery according to claim 7, characterized in that: The mass ratio of the sulfur-containing active material, the high sulfur-soluble polymer, the conductive agent and the lithium salt additive is (60-95):(5-30):(0-10):(0-10).
9. A quasi-solid-state lithium-sulfur battery according to claim 1, characterized in that: The quasi-solid polymer electrolyte further contains a compound additive, wherein the compound additive includes at least one of a sulfide, an oxide, a nitride, a fluoride, and a metal organic framework; The mass ratio of the plasticizer, the low sulfur-soluble polymer and the compound additive is (20-40): (50-80): (0-10), and the concentration of the lithium salt in the weak polar plasticizer reaches (3-8) mol / L.
10. A method for preparing a quasi-solid-state lithium-sulfur battery according to any one of claims 1 to 9, comprising the following steps: S1: The sulfur-containing active material, the high sulfur-soluble polymer, the conductive agent, and the lithium salt additive are uniformly mixed in an organic solvent, and the obtained slurry is coated on the surface of the conductive current collector. After the solvent evaporates, a highly uniform lamellar sulfur-based positive electrode is obtained; S2: High-concentration lithium salt, weak polar plasticizer, low sulfur-soluble polymer and compound additive are mixed evenly in an organic solvent, and the obtained slurry is poured into a flat mold or coated on the surface of the sulfur-based positive electrode. After the solvent evaporates, a thin-film quasi-solid polymer electrolyte with highly uniform properties is obtained; S3: stacking the sulfur-based positive electrode, quasi-solid polymer electrolyte, and lithium-based negative electrode in sequence, and encapsulating them to obtain a quasi-solid-state lithium-sulfur battery.
